2020
DOI: 10.48550/arxiv.2003.11352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryptocurrency Trading: A Comprehensive Survey

Abstract: In the recent years, the tendency of the number of financial institutions including cryptocurrencies in their portfolios has accelerated. Cryptocurrencies are the first pure digital assets to be included by asset managers. Even though they share some commonalities with more traditional assets, they have a separate nature of its own and their behaviour as an asset is still under the process of being understood. It is therefore important to summarise existing research papers and results on cryptocurrency trading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 194 publications
(191 reference statements)
0
9
0
Order By: Relevance
“…Experimenting with logistic regression, SVM, and Naive Bayes, the authors reported that logistic regrssion performed the best and was able to consistently achieve higher than 50% accuracy in predicting next-day Bitcoin price change direction. For a more comprehensive literature review on cryptocurrency trading research, the reader is referred to Fang, Ventre, Basios, Kong, Kanthan, Li, Martinez-Regoband and Wu (2020).…”
Section: Btc Price Prediction With Nlpmentioning
confidence: 99%
“…Experimenting with logistic regression, SVM, and Naive Bayes, the authors reported that logistic regrssion performed the best and was able to consistently achieve higher than 50% accuracy in predicting next-day Bitcoin price change direction. For a more comprehensive literature review on cryptocurrency trading research, the reader is referred to Fang, Ventre, Basios, Kong, Kanthan, Li, Martinez-Regoband and Wu (2020).…”
Section: Btc Price Prediction With Nlpmentioning
confidence: 99%
“…Cryptocurrency as an asset class has also received attention. Fang et al (2021) provide a comprehensive survey of 126 papers studying cryptocurrency trading and risk management. Methodological contributions in this direction include Biais et al (2018) and Pagnotta (2021), who study equilibrium models for pricing of Bitcoin and other decentralized network assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more detailed review of existing literature devoted to research on cryptocurrencies in the context of financial markets is available in Refs. [91,92].…”
Section: Cryptocurrency Tradingmentioning
confidence: 99%